Cultures of childhood: A look at quilombo children - Alves dos Santos, Maria Tarcília; Araújo e Silva, Margareth (Guará Journal, 2024)
The project “Quilombola Community: Identity constitution and school and non-school formative experiences”, registered in the Extension Information System of the Federal University of Goiás – Jataí Regional (PI0116-2016), was developed in the Quilombola Community of Cedro, located in the Municipality of Mineiros, State of Goiás. The study followed the regulations of the Ethics Committee for Research Involving Human Beings (CAAE nº 62116416.9.0000.5083, em conformidade com o precer consubstanciado nº 1.864.576). This work sought to un-derstand the identity composition and school and non-school training experiences of a group of subjects living in the Quilom-bola do Cedro neighborhood, Mineiros, Goiás, based on data collected between the years 2016 and 2022. Considering that we start from paradigms of Psychology and Education, two fiel-ds that have only recently become interested in ethnic studies, it was necessary to complement the theoretical subsidies that support this extension project with anthropological knowled-ge. Thus, the results are the result of the connection between anthropological, psychological and pedagogical knowledge. Deepening theoretical research was important, especially with regard to contextualized human development based on Bron-frenbrenner’s (1996) ecological development theory, which hel-ped create a paradigm shift in educational psychology. Among the results, we highlight the verification of oral culture as a way of transmitting knowledge and values; the relationship with the land and nature as an important non-school training ex-perience; capoeira, an activity very present in the community, as a sporting practice and also a form of cultural expression; as well as the recognition that within each Quilombola child in Cedro, there is a rich social, cultural and historical construction, resulting from a unique and special interpretation that calls for attention and appreciation.